Study guides

☆☆

Q: What is the GCF of 3x - 9x3?

Write your answer...

Submit

Related questions

If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)

The GCF is 9x^2.

9x(x2+3x-10) * * * * * 9x3 + 27x2 - 90x = 9x(x2 + 3x - 10) = 9x(x + 5)(x - 2).

(x + 2)(3x - 1)(3x + 1)

The GCF is 3x.

(3x + 5)(3x^2 + 4)

Since 3x is a factor of 3x^2, it is automatically the GCF.

3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0

You can take a 3x2 out of both of those, leaving 1 and 3x.

Assuming you mean 3x - 2 = 9x - 5...3x - 2 = 9x - 53x + 3 = 9x3 = 6x0.5 = x

= 53 9x3 + 9x2 + 5x1+ 3x1 27 + 18 + 5 + 3

The GCF is 3x.

The GCF is 3.

The GCF is 3.

The GCF is 3x.

The GCF is x.

The GCF is 3.

3X2 - 3X 3X(X - 1) -----------------------factored, so 3X is gfc

The GCF is 3x.

3x

3x

Since 3x is a factor of 3x^2, it is automatically the GCF.

Since 3x is a factor of 12x, it is automatically the GCF.

The GCF of 3 and 6 is 3.The GCF of 3x and 6 is 3.If that's 3x + 6, it factors to 3(x + 2)

(3x2 + 2x + 1)